THE FOLK BELIEFS IN THE TALE OF KIEU AND THE FUNERAL ORATION TO THE SOULS BY NGUYEN DU - Võ Thị Thùy Dung (Tạp chí Khoa học Đại học Đà Lạt)
“The Tale of Kieu” and “The Funeral Oration to the Souls” are two works of great value and significance in the writing career of the great poet, Nguyen Du. The success of these two works not only comes from their content and artistic composition, but also from the life experiences and deep understanding of the national culture expressed fluently in every word. This article explores the impact of folk beliefs; namely, the cult of nature and religious beliefs that are reflected in “The Tale of Kieu” and “The Funeral Oration to the Souls”. Then, it clarifies the role of folk beliefs in both literary and cultural aspects of the works.